2019
DOI: 10.1111/nph.15658
|View full text |Cite
|
Sign up to set email alerts
|

Auxin‐mediated Aux/IAAARFHB signaling cascade regulates secondary xylem development in Populus

Abstract: Summary Wood development is strictly regulated by various phytohormones and auxin plays a central regulatory role in this process. However, how the auxin signaling is transducted in developing secondary xylem during wood formation in tree species remains unclear. Here, we identified an Aux/INDOLE‐3‐ACETIC ACID 9 (IAA9)‐AUXIN RESPONSE FACTOR 5 (ARF5) module in Populus tomentosa as a key mediator of auxin signaling to control early developing xylem development. PtoIAA9, a canonical Aux/IAA gene, is predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 53 publications
(104 reference statements)
4
39
0
Order By: Relevance
“…In this study, the expression profiles of Lelccs (Lelcc13, Lelcc14) were extremely similar to those of LephrA and LephrB. Two genes with similar expression profiles were reported to be regulated by the same transcription factor in Populus [50]. This result indicated that Lelcc13, Lelcc14, and blue-light photoreceptors were regulated by the same transcription factor or had similar functions.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, the expression profiles of Lelccs (Lelcc13, Lelcc14) were extremely similar to those of LephrA and LephrB. Two genes with similar expression profiles were reported to be regulated by the same transcription factor in Populus [50]. This result indicated that Lelcc13, Lelcc14, and blue-light photoreceptors were regulated by the same transcription factor or had similar functions.…”
Section: Discussionsupporting
confidence: 60%
“…The insertion of ve cisgenes encoding gibberellin metabolism or signal proteins affects plant growth [31]. The auxin-mediated Aux/IAA-ARF-HB signal cascade regulates the development of the secondary xylem of poplar [26]. And it was found that a large number of auxin and gibberellin related lncRNA-mRNA coexpression networks were identi ed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hormones, such as auxin, cytokinin, and gibberellin, play an important role in primay and secondary growth [26,27]. In order to further analyze the relationship between lncRNA and plant hormones, we constructed a co-expression network including auxin, cytokinin, and gibberellin related PCgenes and their regulatory lncRNAs (Fig.…”
Section: Lncrnas Involved In the Plant Hormone Biosynthesis Signal Trmentioning
confidence: 99%
“…Stem section (8 µm) was cut on a rotary Leica RM 6025 microtome (Leica), mounted onto Superfrost glass slides (Thermo Fisher), and hybridized with the antisense or sense RNA probes. Hybridization and immunological detection were carried out according to the previous description (Xu C. et al, 2019).…”
Section: In Situ Analysismentioning
confidence: 99%